Effective Communication tools for enriching farmers knowledge - BHARTI, V. K.; BHARTI, SANDEEP; ., SANJAY; ., MEETALI; ., DEEPSHIKHA (Journal of Soil and Water Conservation, 2019)
Development experiences of the last decades have shown that human resources development is essential for food security and market integration. New agricultural technologies are generated by research institutes, universities, private companies, and by the farmers themselves. Agricultural advisory services (including traditional extension, consultancy, business development and agricultural information services) are expected to disseminate new technologies amongst farming community. The role of research and advisory services is to give highly accurate, specific and unbiased technical and management information and advice in direct response to the needs of the farmers. Due to poor linkages between research and advisory services, the adoption of new agricultural technologies by farmers is often very slow and research is not focusing on the actual needs of farmers. In Agricultural Knowledge and Information Systems, people and institutions are linked together to promote and enable mutual learning and generate, share and use agriculture-related technology, knowledge, skills and information. The system integrates farmers, agricultural educators, researchers, extension workers and the private sector to harness knowledge and information from various sources for better farming and improved livelihoods. The areas like; soil fertility, soil health, climate change, environment, effective utilization of water for higher productivity, watershed management, natural resource management, post-harvest technologies, are the burning issues which are to be addressed effectively to farming community in order to enrich and enhance their knowledge.